China and uranium: Comparative possibilities for agency in statecraft in Niger and Namibia - Peter Volberding; Jason Warner (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2017)
This paper asks how the entry of Chinese firms in African uranium markets has impacted the agency of host African states to pursue strategies of economic and social statecraft. Using a comparative case study method with extensive field work, the authors examine how Chinese investment has impacted the uranium sector in both Niger and Namibia and, more critically, the impact investment has had on these states' ability to enact state agency across eight indicators in both economic and social domains. The paper finds that the impact has been mixed and uneven.
Keywords: 330